Kemampuan Caregiver Merawat Klien Skizofrenia di Rumah Sakit Daerah Madani Sulawesi Tengah - Dina Palayukan Singkali; Hanik Endang Nihayati; Hendy Maugiri Margono (FORIKES, 2019)
Several studies have shown the high recurrence rate of schizophrenic clients due to a lack of family abilities as caregivers in caring for clients. The recurrence of schizophrenic clients at the Civil Hospital of Central Sulawesi Province was also due to the role and support of the family. The purpose of this study was to identify the ability of the family to prevent the recurrence of schizophrenic clients at the Central Sulawesi Civil Hospital Hospital. The research design was cross-sectional. The population was the family as a caregiver who treats schizophrenic clients at the Madani Regional Hospital in Central Sulawesi Province from January to February 2019 as many as 85 people. The sampling technique was simple random sampling which was in accordance with the total inclusion criteria of 60 respondents in this study using a questionnaire. Data were analyzed using descriptive analysis. In this study, it was found that the family's ability to prevent recurrence in the less category was caused by the family experiencing burnout in caring for the client. This study can be used as a source of information for nurses in determining interventions in improving family abilities in preventing recurrence of schizophrenic clients. Keywords: ability; care; caregiver; schizophrenia ABSTRAK Beberapa studi menunujukkan tingginya angka kekambuhan klien skizofrenia disebabkan karena kurangnya kemampuan keluarga sebagai caregiver dalam merawat klien. Kekambuhan klien skizofrenai di Rumah sakit daerah madani Provinsi sulawesi Tengah juga disebabkan karena peran dan dukungan keluarga. Tujuan dari penenlitian ini adalah untuk mengidentifikasi kemampuan keluarga mencegah kekambuhan klien skizofrenia di Rumah Sakit daerah madani Provinsi Sulawesi tengah. Design penelitian cross sectional. Populasi yaitu keluarga sebagai caregiver yang merawat klien skizofrenia di Rumah Sakit Daerah Madani Provinsi Sulawesi Tengah pada bulan Januari sampai Februari 2019 sebanyak 85 orang. Teknik pengambilan sampel simple random sampling yang sesuai dengan kriteria inklusi total 60 responden responden Pada penelitian ini menggunakan kuesioner. Data dianalisis menggunakan analisis deskriptif. Pada penelitian ini ditemukan kemampuan keluarga mencegah kekambuhan pada kategori kurang hal ini disebabakan karena keluarga mengalami kejenuhan dalam merawat klien. Penelitian ini dapat dijadikan sumber informasi bagi perawat dalam menentukan intervensi dalam meningkatkan kemampuan keluarga dalam mencegah kekambuhan klien skizofrenia. Kata kunci: kemampuan; merawat; caregiver; skizofrenia